Multitemporal analysis and mapping of land use changes caused by sugar cane expansion in the State of São Paulo, Southeast of Brazil - Carlos Cesar Ronquim; Eduardo Barretto de Figueiredo; Marcelo Fernando Fonseca; Daniela Tatiane de Souza; Guilherme Amorim Ventriche Favero da Silva (Sustentabilidade em Debate)
The change in land use and land cover caused by the expansion of sugar cane in a part of the State of São Paulo between 1988 and 2016 was mapped. The mapping was done automatically using orbital imagery from the Landsat Thematic Mapper (TM) satellite and by manual delimitation of polygons. During the period under study, sugarcane areas more than doubled, expanding by 1.2 million hectares, mainly over pasture, annual crops and citrus. Faced with a shortage of land, the sugar energy sector must increase productivity, but in a sustainable way. To meet this challenge, in addition to increasing productivity per hectare, the sector must expand integrated agricultural practices and promote the conservation of native vegetation. Maps generated from large-scale classification of satellite image time series provide a more detailed understanding of land use dynamics and provide valuable input for land use planning policies.